Aerobic Exercise in Covid-19 Pandemic For A Better Cardiovascular, Respiration, and Body Immunity System - Eka Arum Cahyaning Putri; Lilik Herawati; Yudi Her Oktaviano (Universitas STRADA Indonesia, 2021)
Coronavirus disease 2019 (COVID-19) pandemic is attacking several characteristics of the population. It has been identified that those at higher risk of exposure to COVID-19 are the elderly, patients with hypertension and/or diabetes mellitus, patients with many risk factors and/or have been diagnosed cardiovascular disease, and patients with respiratory diseases. The effects of aerobic exercise during the COVID-19 pandemic need to be systematically structured so that accurate and valid information is delivered, is the aim of this paper. According to the guidelines, aerobic exercise during the COVID-19 pandemic has many benefits, including to improve the performance of the cardiovascular system, to maintain and enhance the performance of the respiratory system and the immune system. Hence, it will have an impact on the individual quality of life, the quality of life increases, people can live a healthy life even during the COVID-19 pandemic.